How different are corporate social responsibility motives in a developing country? Insights from a study of Indian agribusiness firms. (31st July 2018) - Raj, Anup; Kuznetsov, Andrei; Arun, Thankom; Kuznetsova, Olga
Abstract : Against the backdrop of increasing foreign direct investment flows in the developing economies in Asia, the investigation of topical aspects of corporate social responsibility (CSR) in the region increases in importance. We examine the CSR motives of four large indigenous agribusiness firms in India with a view of assessing the validity of the claim that CSR in this country, compared to developed countries, is influenced substantially more by moral, cultural, and religious considerations and less by self‐interest and profit seeking. Unlike numerous other investigations of CSR that rely on questionnaires and company reports, our data are drawn from in‐depth interviews and theme analysis revealing some intricate motives behind CSR behavior and business conditions that inspire them. Our findings challenge some previously reported results and indicate that the degree to which such a behavior is affected by the state of economic development and cultural differences may be smaller than is often argued.